Active deformation of the Central Myanmar Forearc Basin: Insight from post-Pleistocene inversion of the Pyay Fault. Issue 4 (1st December 2020) - Aung, Lin Thu; Oo, Kyaw Zin; Win, Kyaw Myo; Moore, Gregory F.; Tun, Soe Thura; Naing, Win
Highlights: Active inversion of the Pyay Fault represents deformation of this subaerial forearc basin from the Cretaceous to the present. The Pyay Fault is the most significant structure in the Pyay sub-basin, not only for petroleum trapping, but also for the overall development of the Central Myanmar Belt. Uplifted Quaternary river terraces on the hanging wall of the Pyay Fault correspond to its underlying geometries. Sub-surface deformation imaged by 2D seismic reflection profiles and the orientation of fluvial terrace deposits reflect the kinematics and timing of deformation of the Pyay Fault. Pyay Fault is a prime example of active inversion of the Central Myanmar Forearc Basin and plays as a source of earthquake potential of the country. Graphical abstract: Abstract: Pyay sub-basin is located in the southern part of the Central Myanmar Forearc Basin, an elongate belt of en-echelon folds and thrust faults formed as a result of the hyper-oblique convergence of the India and Asia plates. Limited neotectonic studies suggest that the Pyay Fault is a major Pliocene inverted structure that trapped the hydrocarbons in Pyay sub-basin, where only sparse field-based observations are available to address the nature of very recent neotectonic processes. This study focuses on structural deformation related to active inversion of the Pyay Fault using field-based geological observations and interpretations of industrial seismic data. We map the ∼105 km long Pyay Fault, an east- dipping high-angle reverse fault with a significant dextral strike-slip component. The fault underlies the western limb of the major NNW-SSE- striking anticlinal ridge that forms the western margin of Pyay sub- basin. Growth strata within the Pliocene-Pleistocene Irrawaddy Formation, imaged in the shallow part (<1 km) of 2D seismic profiles, reflects the deposition of Pliocene-Pleistocene sediments synchronously with the inversion of the underlying Pyay Fault. In addition, uplifted fluvial terraces of the Ayeyarwady River on the hanging wall of Pyay Fault reflect the post-Pleistocene inversion of the Pyay sub-basin. This study suggests that the Pyay Fault is a prime example of active deformation of the Central Myanmar Forearc Basin which plays an important role in the basin evolution and an earthquake source potential of the Myanmar territory.